2003
DOI: 10.1002/app.13161
|View full text |Cite
|
Sign up to set email alerts
|

Facile synthesis of novel optically active poly(amide‐imide)s containing N,N′‐(pyromellitoyl)‐bis‐l‐phenylalanine diacid chloride and 5,5‐disubstituted hydantoin derivatives under microwave irradiation

Abstract: Pyromellitic dianhydride (1,2,4,5-benzenetetracarboxylic acid 1,2,4,5-dianhydide) (1) was reacted with L-phenylalanine (2) in a mixture of acetic acid and pyridine (3 : 2) at room temperature, then was refluxed at 90 -100°C and N,NЈ-(Pyromellitoyl)-bis-L-phenylalanine diacid (3) was obtained in quantitative yield. The imide-acid (3) was converted to N,NЈ-(Pyromellitoyl)-bis-l-phenylalanine diacid chloride (4) by reaction with thionyl chloride. Rapid and highly efficient synthesis of poly(amide-imide)s (6a-f) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 44 publications
0
23
0
Order By: Relevance
“…[36,37] The polymerization reaction was proceeded by the preparation of optically active pyromellitoyl derivatives (under conventional heating), namely N,N 0 -(pyromellitoyl)-bis-L-phenylalanine diacid chloride and the corresponding L-leucine compound. Starting from these monomers, two series of optically active poly(amide imide)s were investigated: The bis-Lphenylalanine compound was reacted with six differently 5,5-disubstituted hydantoin compounds (Scheme 3a) and a bis-L-leucine derivative with six aromatic diamines, respectively.…”
Section: Poly(amide Imide)smentioning
confidence: 99%
“…[36,37] The polymerization reaction was proceeded by the preparation of optically active pyromellitoyl derivatives (under conventional heating), namely N,N 0 -(pyromellitoyl)-bis-L-phenylalanine diacid chloride and the corresponding L-leucine compound. Starting from these monomers, two series of optically active poly(amide imide)s were investigated: The bis-Lphenylalanine compound was reacted with six differently 5,5-disubstituted hydantoin compounds (Scheme 3a) and a bis-L-leucine derivative with six aromatic diamines, respectively.…”
Section: Poly(amide Imide)smentioning
confidence: 99%
“…N,N -(Pyromellitoyl)-bis(amino acid chloride)s from conversion of benzene-1,2,4,5-tetracarboxylic dianhydride with different amino acids were converted with several aromatic diamines [93][94][95] and hydantoin derivatives (Scheme 8). [96][97][98] Because of the chirality of the employed amino acids, optically active poly(amide-imide)s were obtained. It was shown that the polycondensations were completed after short reaction times (<10 min) under MW conditions.…”
Section: Polyimidesmentioning
confidence: 99%
“…But the microwave heating is a more efficient method for these step-growth polymerization reactions. Faghihi et al [186][187][188] studied synthesis and characterization of optically active PAIs with hydantoin and thiohydantoin derivatives in the main chain via polycondensation reaction of N,N!-(pyromellitoyl)-bis-l-phenylalanine diacid chloride and six different derivatives of 5,5-disubstituted hydantoin compounds in the presence of a small amount of ocresol as a polar organic media. Polymers were synthesized via two different methods: Classical heating and microwave irradiation method.…”
Section: Poly(amide-imide)smentioning
confidence: 99%